2018
DOI: 10.5505/yeditepe.2017.18480
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the frequency and distribution of teeth requiring endodontic treatment and endodontically treated teeth

Abstract: SUMMARY Aim:To determine the distribution and frequency of endodontic treatment and endodontic treatment requirement in permanent teeth. Materials and Methods: Of the 19800 teeth from 775 individuals (age range 16-80 years) were included in the study. All patients were examined clinically and radiologically to determine the teeth requiring endodontic treatment and endodontically treated teeth. For each case, information was collected in a questionnaire including age, gender, education, residence place, income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
3
1
2
Order By: Relevance
“…Results of this study showed that need for endodontic treatment significantly increases with age. This finding is in agreement with other studies (3,8,10,11) and can be related to increased exposure to caries, periodontal problems and restorative procedures leading to root canal treatment and age-related changes of dental pulp complex. In contrast, Umanah et al found that the highest frequency of endodontic treatment was among patients between 20 and 29 years of age (12).…”
Section: Figure 5 Frequency Of Endodontic Emergencies Versus Asymptomatic Conditions Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Results of this study showed that need for endodontic treatment significantly increases with age. This finding is in agreement with other studies (3,8,10,11) and can be related to increased exposure to caries, periodontal problems and restorative procedures leading to root canal treatment and age-related changes of dental pulp complex. In contrast, Umanah et al found that the highest frequency of endodontic treatment was among patients between 20 and 29 years of age (12).…”
Section: Figure 5 Frequency Of Endodontic Emergencies Versus Asymptomatic Conditions Discussionsupporting
confidence: 93%
“…In the present study, root canal treatment was more frequently indicated on maxillary teeth. This result is in agreement with the results of numerous studies (2,8,12,15). Oglah et al assumed that this could also be related to the aesthetic reason, as the upper teeth appear more prominent than the lower teeth during smile, making the patient more interested to preserve the upper teeth (1).…”
Section: Figure 5 Frequency Of Endodontic Emergencies Versus Asymptomatic Conditions Discussionsupporting
confidence: 91%
See 3 more Smart Citations